A century later, still fighting back: antigen‐specific immunotherapies for type 1 diabetes. Issue 5 (11th February 2021) - Rodriguez‐Fernandez, Silvia; Almenara‐Fuentes, Lidia; Perna‐Barrull, David; Barneda, Bruna; Vives‐Pi, Marta
Abstract: Type 1 diabetes (T1D) is a chronic metabolic disease caused by the autoimmune destruction of insulin‐producing β‐cells. Ever since the 1920s, the fate of patients suffering from T1D was dramatically improved owing to the isolation and production of insulin, and the scientific field has largely progressed as a result of the evidence gathered about its underpinnings and mechanisms. The last years have seen this knowledge transformed into actual antigen‐specific immunotherapies with potential to restore selectively the breach of tolerance to β‐cell autoantigens and halt the autoimmune aggression. However, so far, the results of both prevention and reversion trials in T1D have been rather discouraging, so there is still an urgent need to optimize those immunotherapies and their associated factors, for example, posology and administration patterns, route and timing. In this review, we look back on what has been achieved in the last century and identify the main autoantigens driving the autoimmune attack in T1D. Then, we take a deep dive into the numerous antigen‐specific immunotherapies trialed and the ones still at a preclinical phase, ranging from peptides, proteins and agent combinations to gene transfer, nanoparticles, cell‐based strategies and novel approaches exploiting naturally occurring tolerogenic processes. Finally, we provide insight into the several features to be considered in a T1D clinical trial, the ideal time point for intervention and the biomarkers needed for monitoring the successful regulatory effect of the antigen‐specific immunotherapy. Although further research and optimization remain imperative, the development of a therapeutic armamentarium against T1D autoimmunity is certainly advancing with a confident step. Abstract : In this review, we take a deep dive into the numerous antigen‐specific immunotherapies for type 1 diabetes, ranging from peptides, proteins and agent combinations to gene transfer, nanoparticles, cell‐based strategies and novel approaches exploiting naturally occurring tolerogenic processes. Moreover, we provide insight about the several features to be considered in a clinical trial, the ideal time point for intervention and the biomarkers needed for monitoring the successful effect of the immunotherapy. Although further research is required, the development of a therapeutic strategy against type 1 diabetes is certainly advancing with a confident step.